Analisis Prediksi Financial Distress Menggunakan Model Grover (G-Score) dengan Menerapkan Mekanisme Good Corporate Governance di Indonesia - Aisya Shalsha Anggraini; Fauzan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Financial distress is an indication that a company’s finances are not healthy but are still some distance from bankruptcy. Companies can indentify financial problems earlier as a foundation for internal assessment and communication. One of the causes of financial distress is the state of corporate governance. The purpose of this research is to determine the effect of good corporate governance, as proxile by managerial ownership, institutional ownership, an independt board of commissioners, audit committee, and managerial agency costs, on financial distress, as calculated using the Grover (G-Score), in consumer goods industry companies listed on the Indonesia Stock Exchange from 2021 to 2023. The sampling technique uses the purposive sampling method and 60 consumer goods industry companies mer the criteria with 180 data used as research samples. The analytical method used in this research is multiple linear regression analysis using SPSS Version 25. The result showed that Managerial Agency Costs has a significant effect on Financial Distress with the Grover approach. Meanwhile, Managerial Ownership, Institutional Ownership, Independent Board of Commissioners, Audit Committee do not have a signifcicant effect on Financial Distress with the Grover approach.